Efektivitas Pelaksanaan Program Satu Paket Urusan Kependudukan Warga Terpenuhi (SAPUKUWAT) Di Kota Surakarta Sebagai Kota Layak Anak - Dinda Pramitha Shaila Putri; Sri Yuliani (Jurnal Mahasiswa Wacana Publik, 2021)
This study aims to analyze effectiveness implementation of the Satu Paket Urusan Kependudukan Warga Terpenuhi (SAPUKUWAT) program in Surakarta as a Kota Layak Anak (KLA). Beside of that, it also analyze the factors that affect implementation of SAPUKUWAT in Surakarta city as a Kota Layak Anak (KLA). Type of research is descriptive with qualitative methods. Data collection is conducted through interviews, observations and documentation studies. Interviews are conducted to informants with purposive sampling. The data analyzed using Miles and Huberman's interactive model analysis techniques. The target of completing 100% of the birth certificate ownership rate through SAPUKUWAT service has not been able to complete the 100% figure on the number of birth certificate ownership in Surakarta City. For the next, about the factors that affect the implementation of the service program, there are several obstacles, which one is the communication aspect. In the implementation of public awareness still needs to be increased, in order to complete the number of birth certificate ownership. And then about system facility resources that are sometimes crashed. Also on the disposition that still needs to be improved through the responsiveness of Dinas to deal with the system crash.